Simplify 6/7c - 5/9d - 1/2c 1/3d.

a. 5/9c - 4/12d = 5/9c - 1/3d

b. 5/14c - 2/9d

c. 5/9c + 4/122d = 5/9c + 1/3d

d. 5/14c + 2/9d

1 answer

The simplified form of 6/7c - 5/9d - 1/2c 1/3d is:

a. 5/9c - 4/12d = 5/9c - 1/3d
Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions